COMPARATIVE STUDY OF POLYPHENOL, FLAVONOID, AND ANTIOXIDANT ACTIVITY OF VARIOUS MEDICINAL PLANTS COLLECTED FROM DIFFERENT ALTITUDES - BIGYAN JOSHI; NETRA LAL BHANDARI; SUNITA SHRESTHA; RAJENDRA GYAWALI; PANNA THAPA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The main aim of this investigation is to explore the folklore medicinal flora located at Terai and the lesser Himalayan region of Nepal and has a comparative study on phenol, flavonoid, and antioxidant activity that would bring forth a factual basis for its use in the traditional therapy of various health ailments. Methods: Folin-Ciocalteu and Colorimetric aluminum chloride methods were used for the estimation of total polyphenolic and flavonoid content, respectively. Moreover, antioxidant activity was determined by DPPH radical scavenging activity. Results: Among 21 plants collected, Artemesia vulgaris depicted higher (53±0.03 mg GAE/g) and Mimosa pudica (3.7±0.04 mg GAE/g) depicted lower phenolic content whereas the highest flavonoid content is observed in Syzygium cumini and the lowest value in Mentha piperita. Almost all the collected specimen demonstrated antioxidant activity, among which Eupatorium adenophorum and Rhododendron anthopogon demonstrated lower and higher antioxidant activity, respectively. Moreover, phenol and flavonoid content showed a weak correlation with the antioxidant activity indicating the major antioxidant to be different compounds other than phenols or flavonoids. Conclusion: The present study confirms the antioxidant activity of the collected plant specimen and defends its ethnobiological use as a possible natural antioxidant. Furthermore, the result of antioxidant properties encourages their application in medicinal health, functional food, and biopharmaceutics.